1977
DOI: 10.1002/ijc.2910190514
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor immunity in nude mice

Abstract: Tumor implants grew better in radiated or in newborn nu/nu mice than in adult nu/nu controls when, and only when, the tumors were demonstrably immunogenic in normal mice. This result suggests primary immunity. No evidence of immunological memory was found by immunization-challenge type experiments in the nude mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1977
1977
1993
1993

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…It is often said that established nude mouse lines tend to maintain the original histology and function compared to 'in vitro' cell lines because immunological reactivity toward transplanted tumours is too weak to induce the phenotypic and genotypic changes (Prehn & Outzen, 1977;Thomson et al, 1981). This seems to be the case with our nude mouse tumours.…”
Section: Discussionmentioning
confidence: 91%
“…It is often said that established nude mouse lines tend to maintain the original histology and function compared to 'in vitro' cell lines because immunological reactivity toward transplanted tumours is too weak to induce the phenotypic and genotypic changes (Prehn & Outzen, 1977;Thomson et al, 1981). This seems to be the case with our nude mouse tumours.…”
Section: Discussionmentioning
confidence: 91%
“…Irradiation of athymic nude mice has been reported to enhance transplantation of tumor tissue (Prehn and Outzen, 1977;Ohsugi et al, 1980;Watanabe et aL, 1980).…”
Section: Irradiation Of Athymic Nude Micementioning
confidence: 96%
“…
The lack of a test to measure reliably the presence or absence of tumour-associated rejection antigens in humans recently prompted Prehn (1977) to suggest a different type of bioassay. It has become increasingly apparent that allogeneic or xenogeneic tumours do not, in general, grow as well when transplanted into athymic nude mice as when transplanted into the strain of origin.
…”
mentioning
confidence: 99%
“…This is so in spite of the fact that the strain of origin possesses a normal immunological mechanism while the nude mouse cannot reject an allograft of normal tissue. Prehn and Outzen (1977) have demonstrated that allogeneic and animal tumours grow better in nude mice if the animals are X-irradiated. It is probable that X-irradiation would also facilitate the growth of human tumours in nude mice.…”
mentioning
confidence: 99%